Поиск гигантских ДНК-белковых комплексов при помощи ЭВМ - Лукина, Н.И.; Сойдла, Т.Р. (Биополимеры и клетка, 1990)
Созданы две программы для выявления и визуализации пространственной асимметрии ДНК. С их помощью анализировали 2 мкм плазмиду дрожжей-сахаромицетов. Выявлен участок особой ориентации G—С-пар. Расположение этого участка совпадает с локализацией ненуклеосомного ДНК-белкового комплекса, выявленного ранее в экспериментальной работе. Созданные программы могут быть использованы для поиска крупных ДНК-белковых комплексов. Створено дві програми для виявлення та візуалізації просторової асиметрії ДНК. З їхньою допомогою проаналізовано 2 мкм плазміду дріжджів-сахароміцетів. Виявлено ділянку особливої орієнтації G–С-пар. Розташування цієї ділянки збігається з локалізацією ненуклеосомного ДНК-білкового комплексу, виявленого раніше в експериментальній роботі. Створені програми можуть бути використані для пошуку великих ДНК-білкових комплексів. Two simple programs to detect extensive spatial asymmetries of DNA were created. The programs were used to study the 2 u,m plasmid of Saccharomyces yeast. A nearly 600 bp. uninterrupted region of special spatial orientation of G-C base pairs was found covering the REP 3 locus. The anomaly was obvious when estimating the helix lead approx. 104.4 (but not at 1 ,10:0 or 10.6). It is supposed that the region corresponds to a giant non-nucleosomal DNA-protein complex supposedly of an «oozing» mechanism according to the classification by Ptashne (19*86). The complex is also indicated by some recent experimental results. The new programs can be used for searching giant DNA-protein complexes.